SOCIO-ECONOMIC ASPECTS OF THE CONCEPT OF SUSTAINABLE DEVELOPMENT IN AZERBAIJAN REPUBLIC - Z. T. Imrani; M. R. Musayeva (Юг России: экология, развитие)
Aim. The aim is to determine the socio-economic aspects of sustainable development of the Republic of Azerbaijan taking into account economic, environmental, social and environmental opportunities of the country; to find the rationale for the concept of sustainable development to eliminate major differences specific to regional economic development, management of economic and social development of the regions.Methods. Historical and comparative analysis, system approach, analysis of statistical and mathematical materials.Findings. We identified the advantages of the concept of sustainable development; cunducted the analysis of the dynamics of development of the leading industries in the region; studied the most promising sectors of the regions from the economic and geographic point of view.Conclusion. We identified socio-economic aspects of sustainable development of the Republic of Azerbaijan.